2006
DOI: 10.1007/s00213-006-0400-9
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor effects of pergolide, a dopamine agonist, in healthy subjects: a lateralized readiness potential study

Abstract: The results indicate that dopaminergic neurotransmission effectively modulates early perceptual and cognitive stages of information processing as suggested by neural network models of the functional role of prefrontal DA. The lack of an effect on aspects of motor processing may be due to a higher capacity of the nigrostriatal compared to the mesocortical DA system to compensate pharmacologically induced changes in dopaminergic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 73 publications
(97 reference statements)
0
12
0
Order By: Relevance
“…Together with a correlation of increased omission errors with larger motor PINV’ amplitudes [36], these findings suggest that reduced attention may be associated with reduced iMP’ (less motor preparation) but increased mPINV’ (compensatory post-processing). Additionally, we hypothesized to find stimulant effects, which would specifically affect mPINV’ but not iMP’ amplitude (because dopaminergic medication in previous studies affected only lateralized post-movement potentials [31], [32]), pointing to medication-related compensation processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with a correlation of increased omission errors with larger motor PINV’ amplitudes [36], these findings suggest that reduced attention may be associated with reduced iMP’ (less motor preparation) but increased mPINV’ (compensatory post-processing). Additionally, we hypothesized to find stimulant effects, which would specifically affect mPINV’ but not iMP’ amplitude (because dopaminergic medication in previous studies affected only lateralized post-movement potentials [31], [32]), pointing to medication-related compensation processes.…”
Section: Introductionmentioning
confidence: 99%
“…MRP could reflect an excellent neurophysiological marker to monitor the effects of stimulant medication in ADHD [29], [30]. During movement execution, lateralized MRP amplitudes (iMP’) seem rather independent of dopaminergic medication [31], [32]. In contrast, mPINV amplitude has been found to be affected by first generation antipsychotics (dopamine antagonists) [33].…”
Section: Introductionmentioning
confidence: 99%
“…Shorter subsecond time-interval timing, however, appears to be more specifically modulated by dopaminergic activity (Rammsayer & Stahl 2006).…”
Section: Psychostimulants and Effects On Timingmentioning
confidence: 99%
“…Given the evidence for dopamine involvement in subsecond time discrimination (Rammsayer 1993;Rammsayer & Stahl 2006), we used a discrimination task of temporal differences of hundreds of milliseconds which has shown to elicit deficits in ADHD children (Smith et al 2002;Rubia et al 2007a). The task activates key timing regions of right dorsolateral and inferior prefrontal cortices, the cerebellum, ACG and the SMA in adults and children (Smith et al 2003, and elicits underactivation in ADHD adolescents in right lateral prefrontal cortex, ACG and SMA ( §3; figure 1b; Smith et al 2008).…”
Section: New Data: Effects Of Mph On Brain Dysfunction In Adhd Duringmentioning
confidence: 99%
“…Furthermore, Rammsayer and Stahl [58] found that dopamine agonists facilitated early cognitive and perceptual aspects of sensorimotor processing such that the time required for early stimulus processing was reduced.…”
Section: Generalizability To Other Domainsmentioning
confidence: 99%